FROM FORMAL VALIDITY TO ETHICAL ACCOUNTABILITY: GOOD FAITH IN SHARIA ELECTRONIC CONTRACTS UNDER INDONESIAN LAW - Nugraha, Sigit Nurhadi; Budiono, Abdul Rachmat; Santoso, Budi; Sulistyarini, Rachmi (JURNAL HAKAM, 2025)
The expansion of electronic contracts has significantly transformed sharia-based transactions in the digital sphere, yet the prevailing legal framework remains largely anchored in formal validity. Indonesian contract law and the Law on Electronic Information and Transactions (ITE Law) primarily assess contract enforceability through formal requirements and the legal recognition of electronic documents, offering limited tools to evaluate the ethical quality of consent formation. In contrast, Islamic economic law, as articulated in the Compilation of Sharia Economic Law (KHES) and the fatwas of the National Sharia Council (DSN-MUI), emphasizes trustworthiness, transparency, and substantive justice, but lacks operational parameters suited to digital transactions. This normative gap constitutes the central problem addressed in this article. The study aims to reconceptualize good faith as ethical accountability and to formulate a parameter-based model for assessing sharia electronic contracts. Employing normative legal research with statutory and conceptual approaches, the analysis draws upon Indonesian contract law, the ITE Law, KHES, DSN-MUI fatwas, and relevant legal doctrines. The findings demonstrate that good faith should be repositioned from a post-dispute corrective principle to an ex ante standard of ethical accountability governing contract formation. The article formulates five key parameters of good faith: substantive transparency of information, fairness of electronic consent processes, balance of bargaining power, consistency between pre-contractual representations and contract performance, and prevention of exploitative gains. This model contributes to the literature by bridging the fragmentation between positive contract law, digital regulation, and sharia principles. Practically, it offers a substantive framework for consumer protection and sharia compliance in Islamic fintech and digital marketplaces.